A Colon-Targeted Prodrug, 4-Phenylbutyric Acid-Glutamic Acid Conjugate, Ameliorates 2,4-Dinitrobenzenesulfonic Acid-Induced Colitis in Rats - Kim, Soojin (Pharmaceutics, 2020)
An elevated level of endoplasmic reticulum (ER) stress is considered an aggravating factor for inflammatory bowel disease (IBD). To develop an ER-stress attenuator that is effective against colitis, 4-phenylbutyric acid (4-PBA), a chemical chaperone that alleviates ER stress, was conjugated with acidic amino acids to yield 4-PBA-glutamic acid (PBA-GA) and 4-PBA-aspartic acid (PBA-AA) conjugates. The PBA derivatives were converted to 4-PBA in the cecal contents, and the conversion was greater with PBA-GA than that with PBA-AA. After oral administration of PBA-GA (oral PBA-GA), up to 2.7 mM PBA was detected in the cecum, whereas 4-PBA was not detected in the blood, indicating that PBA-GA predominantly targeted the large intestine. In 2,4-dinitrobenzenesulfonic acid-induced colitis in rats, oral PBA-GA alleviated the damage and inflammation in the colon and substantially reduced the elevated levels of ER stress marker proteins in the inflamed colon. Moreover, PBA-GA was found to be as effective as the currently used anti-IBD drug, sulfasalazine. In conclusion, PBA-GA is a colon-targeted prodrug of 4-PBA and is effective against rat colitis probably via the attenuation of ER stress in the inflamed colon.